Statistics of Biomass Structure of Dendrocalamus strictus (Roxb.) Nees Seedlings - Kumar, Rakesh; Pandey, Rajiv; Pal, Mohinder (Indian Forester, 2000)
Descriptive statistics of different biomass and growth parameters of Dendrocalamus strictus seedlings were reported. The relative contributions of different parts of seedlings to total weight in fresh and dry conditions were also given. It was observed that the contribution of culms was maximum followed by rhizome for both the conditions. An estimate of every parameter is also worked out for different number of culms present in a clump. Similar trend was observed for the seedlings having 3 and 4 number of culms per clump for most of the parameters.